USULAN PENGENDALIAN KUALITAS DENGAN ESTIMASI TINGKAT KEGAGALAN PROSES (DPMO) - Aribowo, Budi (Industrial and Systems Engineering Assessment Journal (INASEA), 2004)
Article discusses an alternative quality control that has the same function with controlling map that has been known by the industry society but the suggested controlling map is offering a new approach, that is using the value of DPMO (Defect Per Millions). Procedure and view of DPMO and the suggested graphic control, hopefully can become suplement for the existent of controlling map so preventive action can be done and company can estimate the quality cost.